Violence and the City of Istanbul - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
The city of Istanbul historically witnessed many cases of violence. The nature of the violence changed with times and its aggravation had seasons, while some violence was almost always present in some form or another. Being a cosmopolitan urban center, violence seems to be one of the additives in the city's very essence and nature. (C) 2015 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license.
Keywords: City; cosmopolite; violence; juvenile delinquency; drug use